Estudo de supressão de múltiplas utilizando deconvolução preditiva no domínio Ƭ – P em um dado 2D marinho - ARAÚJO, Felipe Gusmão (2020)
A great part of seismic processing is based on multiple reflection attenuation. This step is essential to take off the noise on the data, avoiding mistakes to identify reflectors during seismic interpretation. On this paper was applied predictive deconvolution on the Ƭ – P domain to a 2D real marine data, attenuating the free surface multiples. The results are analyzed considering the effectiveness of the predictive deconvolution utilizing different parameters.